Probing Zinc–Protein–Chelant Interactions Using Gold Nanoparticles Functionalized with Zinc‐Responsive Polypeptides. (17th July 2014) - Mak, Wing Cheung; Selegård, Robert; Garbrecht, Magnus; Aili, Daniel
<x xml:space="preserve">Abstract</x> The coordination of zinc by proteins and various other organic molecules is essential for numerous biological processes, such as in enzymatic catalysis, metabolism, and signal transduction. Presence of small molecular chelants can have a profound effect on the bioavailability of zinc and affect critical Zn2+–protein interactions. Zn2+ chelators are also emerging therapeutics for Alzheimer's disease because of their preventive effect on zinc‐promoted amyloid formation. Despite the importance of zinc–protein–chelant interactions in biology and medicine, probing such interactions is challenging. Here, an innovative approach is introduced for real‐time characterization of zinc–protein–chelant interactions using gold nanoparticles (AuNPs) functionalized with a zinc‐responsive protein mimetic polypeptide. The peptide‐functionalized AuNPs aggregate extensively in the presence of Zn2+, triggered by specific Zn2+‐mediated polypeptide dimerization and folding, causing a massive red shift of the plasmon band. Chelants affects the Zn2+–polypeptide interaction and thus the aggregation differently depending on their concentrations, zinc‐binding affinities, and coordination numbers, which affect the position of the plasmon band. This system is a simple and powerful tool that provides extensive information about the interactions of chelants in the formation of Zn2+ coordination complexes, and an interesting platform for development of bioanalytical techniques, and characterization of chelation‐based therapeutics.